Writing against oneself: Chabani Manganyi as a Black autobiographical subject - Mokoena, Hlonipha (PINS-Psychology in Society, 2024)
As a postcolonial society, it could be said — without fear of exaggeration — that South Africa has by far produced the most “life writing” or “autobiographical” writing. Of course, this didn’t begin with the end of apartheid but it is also complicated to write or think about this genre as anything but part of our postcolonial condition.